Fabrication of high-strength Ti materials by in-process solid solution strengthening of oxygen via P/M methods - Sun, Bin; Li, Shufeng; Imai, Hisashi; Mimoto, Takanori; Umeda, Junko; Kondoh, Katsuyoshi (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2013)
The applications of Ti and its alloys are limited to high-performance products because of the expensive material cost and poor plastic formability. In order to develop a cost-effective processing route for pure Ti and its alloys, pure Ti powder was used as raw material and consolidated by different powder metallurgy routes in this study. Warm compaction and cold compaction were employed to consolidate Ti powder and spark plasma sintering (SPS) was used as a reference method. The obtained compacts were hot extruded subsequently. The microstructures and mechanical properties of the hot-extruded pure Ti were evaluated. It was found that the samples prepared by warm compaction showed a higher ultimate tensile strength of 973.6MPa, a better elongation of 26% and a higher Vickers hardness of 389.8Hv compared with the other two methods. Effects of grain orientation, grain refinement and solid solution strengthening on mechanical properties were discussed. It was found that the main strengthening mechanism for the sample prepared by warm compaction was oxygen solid solution strengthening resulting from in-process in this study. The strengthening effect of oxygen solid solution was calculated as 769.8MPa/mass% [O].